1977
DOI: 10.1002/polc.5070610104
|View full text |Cite
|
Sign up to set email alerts
|

State conditions of polymer and monomer with liquid crystalline phases

Abstract: SYNOPSISRcsults are presented for studies of p-substituted p'-3cryloyloxy-azoxy-bcnzcnc, cholesteryl vinyl-succinate. and cholesteryl vinyl fumaratc in systems containing monomers and polymers in diffcrcnt mesomorphic states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The transition heats and temperatures resulting from reaction are shown in Table IV. Representative DSC thermograms, as a function of reaction time, are illustrated in Figures [10][11][12] for the ~75 wt % composition for each initial molecular weight of BPE/I/N20. The reaction temperature of 220 °C is an effective annealing tempera- " Glass-transition temperature estimated by DSC (10 °C/min).…”
Section: Resultsmentioning
confidence: 99%
“…The transition heats and temperatures resulting from reaction are shown in Table IV. Representative DSC thermograms, as a function of reaction time, are illustrated in Figures [10][11][12] for the ~75 wt % composition for each initial molecular weight of BPE/I/N20. The reaction temperature of 220 °C is an effective annealing tempera- " Glass-transition temperature estimated by DSC (10 °C/min).…”
Section: Resultsmentioning
confidence: 99%
“…34 The structure of the synthesized polymers was confirmed by FT-IR and NMR spectroscopy. Investigation of the obtained polymer by means of FT-IR spectroscopy indicated that the substitution reaction of P1 with the heterocyclic amines (2 -4) could be achieved.…”
Section: Structural Characterizationmentioning
confidence: 97%
“…Different smectic states corresponding to folded chains as well as nematic and cholesteric structures of polymers prepared from mesogenic compounds connected with flexible chain segments were identified by miscibility investigations (24,37). The results of miscibility investigations were negative for polymers containing mesogenic groups in the side chains connected directly to the main chain (9)(10)(11)16). With mesogenic side chains connected to the main chain by flexible chains, called a "spacer" (6,14^1-23,44,46,47pi), smectic state polymers were observed.…”
Section: Introductionmentioning
confidence: 99%